1996
DOI: 10.1080/095530096145445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the yields of translocations and dicentrics measured using conventional Giemsa staining and chromosome painting

Abstract: Inconsistent results have been reported regarding the yields of translocations and dicentrics measured using chromosome painting. This inconsistency may be due to mis-scoring of dicentrics as translocations because painting is unsuited to identify centromere positions. In the present study, chromosome aberrations exclusively in the first mitosis after irradiation were analyzed using human peripheral lymphocytes. When identical metaphases were analyzed by both painting and conventional Giemsa staining, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…1990; 1.5-2 fold, Natarajan et al 1992; 1-3 fold, Tucker et al 1993;1.67-4 fold, Boei et al 1996; greater than 1, VirsikPeuckert et al 1997;1.4 fold, Finnon et al 1995;1.3-3.75 fold, Luomahaara et al 1999;1.55-2.79 fold, Schmid et al 1992;1.11-3.67 fold, Bauchinger et al 1993; an observed high number in translocations at most dose points, Nakano et al 1993;1.2 fold, Knehr et al 1999). A study previously reported from our laboratory (Kanda et al 1996), in which cells in the second division and misclassification of aberrations were carefully excluded, also showed a slightly higher number of translocations, although the difference was not statistically significant. Natarajan et al 1994 suggested the difference in the mechanisms of the misrepair process as a possible explanation for the high incidence of translocations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…1990; 1.5-2 fold, Natarajan et al 1992; 1-3 fold, Tucker et al 1993;1.67-4 fold, Boei et al 1996; greater than 1, VirsikPeuckert et al 1997;1.4 fold, Finnon et al 1995;1.3-3.75 fold, Luomahaara et al 1999;1.55-2.79 fold, Schmid et al 1992;1.11-3.67 fold, Bauchinger et al 1993; an observed high number in translocations at most dose points, Nakano et al 1993;1.2 fold, Knehr et al 1999). A study previously reported from our laboratory (Kanda et al 1996), in which cells in the second division and misclassification of aberrations were carefully excluded, also showed a slightly higher number of translocations, although the difference was not statistically significant. Natarajan et al 1994 suggested the difference in the mechanisms of the misrepair process as a possible explanation for the high incidence of translocations.…”
Section: Introductionmentioning
confidence: 93%
“…The Giemsa staining was washed out with acetic alcohol. The slides were processed following the method reported by Kanda et al 1996. Chromosome painting by FISH with composite whole chromosome-specific DNA libraries for human chromosomes 2 and 4 (Cambio, Cambridge, UK) was performed according to the method described by Yamada et al 1996 with a slight modification.…”
Section: Image Acquisition Of Chromosome Rearrangementsmentioning
confidence: 99%
“…Many authors found the ratio to be higher than unity (Natarajan et al , Schmid et al 1992, Bauchinger et al 1993, whereas others reported a ratio equal to 1 (Nakano et al 1993, Tucker et al 1993, Kovacs et al 1994, Fernandez et al 1995, Kanda and Hayata 1996, Lloyd et al 2001. The reasons for the inconsistent results are not known.…”
Section: Ratios Of 2b To 2a In Painted Chromosomesmentioning
confidence: 73%
“…ring-like fragments turned sideways and small, round fragments without a hole were excluded. After observation by light microscopy, some slides were destained with methanol-acetic acid, treated with RNase A and pepsin, post-fixed in formaldehyde solution and processed for hybridization according to a dual-staining method developed for the successive application of Giemsa staining and fluorescence in-situ hybridization (FISH) painting in the same metaphase (Kanda and Hayata 1996). The centromeric regions of all human chromosomes were labelled with biotinylated human alpha satellite DNA probe (Cambio, Cambridge, UK) conjugated with avidin-FITC (Roche Diagnostics KK, Tokyo, Japan).…”
Section: Slide Preparationmentioning
confidence: 99%